Myeloid derived suppressor cells are present at high frequency in neonates and suppress in vitro T cell responses. - Ana Gervassi; Nicholas Lejarcegui; Sandra Dross; Amanda Jacobson; Grace Itaya; Elvis Kidzeru; Soren Gantt; Heather Jaspan; Helen Horton (PLoS ONE, 2014)
Over 4 million infants die each year from infections, many of which are vaccine-preventable. Young infants respond relatively poorly to many infections and vaccines, but the basis of reduced immunity in infants is ill defined. We sought to investigate whether myeloid-derived suppressor cells (MDSC) represent one potential impediment to protective immunity in early life, which may help inform strategies for effective vaccination prior to pathogen exposure. We enrolled healthy neonates and children in the first 2 years of life along with healthy adult controls to examine the frequency and function of MDSC, a cell population able to potently suppress T cell responses. We found that MDSC, which are rarely seen in healthy adults, are present in high numbers in neonates and their frequency rapidly decreases during the first months of life. We determined that these neonatal MDSC are of granulocytic origin (G-MDSC), and suppress both CD4+ and CD8+ T cell proliferative responses in a contact-dependent manner and gamma interferon production. Understanding the role G-MDSC play in infant immunity could improve vaccine responsiveness in newborns and reduce mortality due to early-life infections.